2021
DOI: 10.1111/jcmm.16739
|View full text |Cite
|
Sign up to set email alerts
|

The human amniotic fluid stem cell secretome triggers intracellular Ca2+ oscillations, NF‐κB nuclear translocation and tube formation in human endothelial colony‐forming cells

Abstract: Second trimester foetal human amniotic fluid‐derived stem cells (hAFS) have been shown to possess remarkable cardioprotective paracrine potential in different preclinical models of myocardial injury and drug‐induced cardiotoxicity. The hAFS secretome, namely the total soluble factors released by cells in their conditioned medium (hAFS‐CM), can also strongly sustain in vivo angiogenesis in a murine model of acute myocardial infarction (MI) and stimulates human endothelial colony‐forming cells (ECFCs), the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…Likewise, NAADP-AM, a membrane-permeable analogue of NAADP, could induce either a transient elevation in [Ca 2+ ] i or a burst of intracellular Ca 2+ oscillations. This latter observation is in accord with the evidence that: 1) intracellular delivery of NAADP may induce oscillatory Ca 2+ signals in human Jurkat T-lymphocytes (Berg et al, 2000), cytotoxic T lymphocytes (Davis et al, 2012), and human pancreatic β-cells (Johnson and Misler, 2002); 2) NAADP contributes to agonist-induced repetitive Ca 2+ spikes in several types of endothelial cells (Zuccolo et al, 2019;Berra-Romani et al, 2020;Balducci et al, 2021), and that 3) NAADP induces intracellular Ca 2+ oscillations in mouse cardiomyocytes during reperfusion injury (Davidson et al, 2015). Early work conducted on echinoderms first suggested that NAADP was able to elicit repetitive Ca 2+ oscillations by promoting a Ca 2+ -dependent crosstalk between two different Ca 2+ pools (Churchill and Galione, 2001), which were later shown to be located in acidic vesicles and ER (Churchill et al, 2002;Moccia et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, NAADP-AM, a membrane-permeable analogue of NAADP, could induce either a transient elevation in [Ca 2+ ] i or a burst of intracellular Ca 2+ oscillations. This latter observation is in accord with the evidence that: 1) intracellular delivery of NAADP may induce oscillatory Ca 2+ signals in human Jurkat T-lymphocytes (Berg et al, 2000), cytotoxic T lymphocytes (Davis et al, 2012), and human pancreatic β-cells (Johnson and Misler, 2002); 2) NAADP contributes to agonist-induced repetitive Ca 2+ spikes in several types of endothelial cells (Zuccolo et al, 2019;Berra-Romani et al, 2020;Balducci et al, 2021), and that 3) NAADP induces intracellular Ca 2+ oscillations in mouse cardiomyocytes during reperfusion injury (Davidson et al, 2015). Early work conducted on echinoderms first suggested that NAADP was able to elicit repetitive Ca 2+ oscillations by promoting a Ca 2+ -dependent crosstalk between two different Ca 2+ pools (Churchill and Galione, 2001), which were later shown to be located in acidic vesicles and ER (Churchill et al, 2002;Moccia et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Arachidonic acid is a conditionally essential polyunsaturated fatty acid that, in endothelial cells, plays a crucial role in regulating NO release and angiogenesis [ 43 , 96 , 97 ]. Arachidonic acid is cleaved by glycerophospholipids on the plasma membrane or the nuclear envelope by phospholipase A2 (PLA2), PLC, and phospholipase D (PLD) ( Figure 1 ) [ 98 ] and may be metabolized into an impressive array of bioactive eicosanoids, e.g., prostanoids, thromboxane, leukotrienes, and epoxyeicosatrienoic acids (EETs) ( Figure 1 ), by three distinct families of enzymes, respectively: COXs, LOXs, and CYP ω-hydroxylases and epoxygenases [ 98 , 99 ].…”
Section: Ros Production and Elimination In Endothelial Cellsmentioning
confidence: 99%
“…Thus, SOCE regulates most of endothelial functions, ranging from NO release and vWF secretion to the control of endothelial permeability and proliferation [ 9 , 26 , 166 , 167 , 168 ]. Similarly, SOCE is crucial to ensure proper intracellular Ca 2+ signaling in circulating ECFCs recruited to ischemic tissues to participate in vascular regrowth [ 97 , 111 , 169 ]. The molecular makeup of endothelial SOCE may change depending on the vascular bed, but briefly addressing this controversial issue is necessary to understand how redox signaling regulates agonist-evoked extracellular Ca 2+ entry in the endothelial lineage.…”
Section: Ros Modulate Store-operated Ca 2+ Entry In Vascular Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, EVs concentrated from the human amniotic fluid progenitor secretome have been attracting increasing interest lately; the EV yield obtained from human hAF-MSC has been proven to be higher than human bone marrow-MSC [ 46 ]. Several independent studies have reported that the hAF-MSC and hAFSC secretome exert pro-survival, anti-apoptotic effects [ 47 ], while quenching inflammation [ 48 ], stimulating local angiogenesis [ 49 , 50 ], and supporting cardiac protection following myocardial infarction or cardiotoxicity [ 49 , 51 , 52 , 53 ]. In this scenario, hAFSC-EVs have been widely profiled to assess whether they can recapitulate such pro-regenerative potential with promising results in preclinical models of skeletal and cardiac muscle injury [ 19 , 47 , 49 , 54 ], lung [ 55 ] and neurodegenerative disease [ 56 , 57 ], osteoarthritis [ 58 ], osteoporosis [ 59 ] and cutaneous injury [ 60 ].…”
Section: Introduction: Human Amniotic Fluid Stem Cells As Reservoir Of Paracrine Factorsmentioning
confidence: 99%